Upaya Mitigasi Spiritual Dalam Menyikapi Pandemi Corona Virus Diseases (Covid-19) Menurut Lontar Roga Sanghara Bhumi - Anak Agung Gde Oka Widana; Nurul Faidah (Kamaya: Jurnal Ilmu Agama, 2021)
The phenomenon of the Corona Virus Diseases (Covid-19) Pandemic that has occurred in all corners of the world has made the world's internal situation very worrying. However, if you are willing to look back at your historical track record, situations similar to the Covid-19 pandemic have actually been experienced by the world, such as SARS-Coronavirus and MERS-Coronavirus. All of these phenomena have been studied in medical laboratories, but what is very rarely done is an assessment based on existing historical records or data, as in classical Lontar literature as in Lontar Roga Sanghara Bhumi. Three issues were raised in this study: regarding the structure of the text, classifying the Covid-19 pandemic disaster from the Lontar Roga Sanghara Bhumi study and spiritual mitigation efforts in responding to the Covid-19 pandemic disaster from the Lontar Roga Sanghara Bhumi study. This type of research is a qualitative research with a psychological approach. The data obtained were collected using library techniques and document recording. The data that has been collected is then analyzed with qualitative descriptive techniques and hermeneutics. The results of this study indicate that the content structure is structured in the format of formal structure (manggala, corpus, epilogue, language) and narrative structure (theme and aspects of speech). If classified, the Covid-19 disaster in the text of Lontar Roga Sanghara Bhumi is included in a Non-Natural Disaster, which is categorized as a Grubug Agung phenomenon or a pandemic outbreak on a wide scale. There are several spiritual mitigation efforts in responding to Covid-19 according to Lontar Roga Sanghara Bhumi, including; (1) Preventive Efforts, in the form of spiritual-based isolation and social distancing efforts, drawing closer to God and fortifying oneself with spiritual means, (2) Curative Efforts, in the form of alternative treatments with tattwa and spiritual ethics as well as through ritual means (yajña), and (3) Promotive Efforts, in the form of suggestions to deepen the knowledge of God, ethics and morality, yaja and deepen the knowledge of usada